Maestro of the SereNADe: SLC25A51 Orchestrates Mitochondrial NAD+. Issue 5 (May 2021) - Ouyang, Yeyun; Bott, Alex J.; Rutter, Jared
Abstract : Recently, three groups, Girardi et al., Kory et al., and Luongo et al., independently identified solute carrier (SLC) 25A51 as the long-sought, major mitochondrial NAD + transporter in mammalian cells. These studies not only deorphan an uncharacterized transporter of the SLC25A family, but also shed light on other aspects of NAD + biology.